RADT-38. INCIDENCE OF HEARING IMPAIRMENT AFTER DEFINITIVE PROTON BEAM THERAPY FOR MALIGNANCIES OF THE BRAIN AND BASE OF SKULL. (14th November 2022) - Gaito, Simona; Hwang, Eunji; Aznar, Marianne; Ahern, Verity; Twaithes, David; France, Anna; Sitch, Peter; Indelicato, Daniel J; Holtzman, Adam; Pan, Shermaine; Smith, Ed; Whitfield, Gillian
Abstract: AIM: Aim of the project is to report the incidence of moderate/severe (G ≥ 3) long-term hearing impairment (HI) and to identify risk factors in patients treated for malignancies of the brain and base of skull with definitive Proton Beam Therapy (PBT) within the Proton Overseas Programme (POP). METHODS: Clinical and treatment-related data from patients' files stored in a national database and curated by a dedicated outcomes unit were extracted and analysed. Clinical toxicity data from the POP were graded as per Common Terminology Criteria for Adverse Events (CTCAE 4.0). Dosimetric data (Dmean to the cochlear structures) were extracted from the Treatment Planning System Proknow. For the purpose of this analysis, patients with radical definitive PBT only were selected. RESULTS: Between 2008 - 2018, 229 UK patients received radical PBT overseas for Craniopharyngioma (104 patients;45.4%), Chordoma (60; 26.2%), Chondrosarcoma (53;23.1%), Meningioma (7;3%), Pituitary Adenoma (5;2.1%). Median age was 17 years (1-77). Median prescription dose was 55.8 Gy (45-75.8). Median dose to the Left and Right cochleas were 14.18 Gy (0-85.15) and 12.55 Gy (0-77.50), respectively. Eight patients developed G ≥ 3 HI (3.5%). Of those, 7 had received dose escalated treatments for radioresistant tumours (chordomas or condrosarcomas). In 4/8, the HI was bilateral. The median cochlear dose for the structures who developed G ≥ 3 HI was 48.99 Gy (10-76.87). CONCLUSIONS: Incidence of G ≥ 3 HI in this patient population compares with historical cohorts, and, as expected, is higher in patients who receive dose escalated treatments for radioresistant tumours of the base of skull. Median dose in those who developed HI supports the use of dose constraints used in the clinical PBT practice.